Serum Gamma-Glutamyltransferase and the Risk of Hyperuricemia: A 6-Year Prospective Study in Japanese Men - Nakamura, K.; Sakurai, M.; Miura, K.; Morikawa, Y.; Nagasawa, S.; Ishizaki, M.; Kido, T.; Naruse, Y.; Suwazono, Y.; Nakagawa, H. (Hormone and Metabolic Research, 2012)
We conducted a longitudinal study to investigate whether increased serum gamma-glutamyltransferase independently predicts subsequent development of hyperuricemia. The study participants included 3 310 Japanese men without hyperuricemia, aged 20–54 years. The participants had annual heath examinations for 6 years to assess incident hyperuricemia (defined as serum uric acid>416.4 μmol/l and/or taking medication for hyperuricemia). The risk of incident hyperuricemia was compared in participants grouped according to their baseline serum gamma-glutamyltransferase level. During follow-up, there were 529 incident cases of hyperuricemia. A positive, dose-response relationship was observed between serum gamma-glutamyltransferase and the risk of incident hyperuricemia. The hazard ratios (95% confidence intervals) for hyperuricemia, compared with a serum gamma-glutamyltransferase level≤19 U/l, were 1.32 (1.05–1.67) for 20–39 U/l, 1.28 (0.90–1.83) for 40–59 U/l, 1.56 (0.98–2.47) for 60–79 U/l, and 1.57 (1.02–2.41) for ≥80 U/l after adjustment for baseline serum uric acid, creatinine, total cholesterol, and glycated hemoglobin levels, ln(serum alanine aminotransferase), age, systolic blood pressure, medications for hypertension, hypercholesterolemia, and diabetes, body mass index, and smoking and exercise habits. A similar positive relationship was observed regardless of the presence or absence of alcohol drinking, obesity, metabolic disorders (any combination of hypertension, hypercholesterolemia and/or diabetes), or clinically high serum aminotransferases, without evidence of a significant interaction between increased serum gamma-glutamyltransferase and risk factors for incident hyperuricemia. These findings indicate that increased serum gamma-glutamyltransferase is an independent predictor of subsequent development of hyperuricemia.
Keywords: gamma-glutamyltransferase; aspartate aminotransferase; alanine aminotransferase; hyperuricemia; epidemiology